How much control do firms exercise over their resources when entering emerging markets? - Claudio Giachetti; Augustine Awuah Peprah (BRQ Business Research Quarterly, 2022)
The international management literature has presented inconclusive results about the effect of institutional voids in a host country on entrant firms' resource commitment. With the lens of institutional theory and transaction cost theory, this article examines how institutional voids in an emerging market influence a firm's decision to move resources in that market. Resource commitment in an emerging market is examined in terms of the degree of control of the entry strategy employed. The theory presented argues that as institutional voids in a firm's host country escalate, the firm sets out different priority actions to mitigate behavioral and environmental uncertainties in the host country, that in turn affect the degree of control of its entry modes. By relying on a sample of 90 Italian firms operating in China between 2001 and 2010, the results support the hypothesis that the institutional voids-entry mode degree of control relationship displays an inverted U-shape.
Keywords: F23; L1; 650; Institutional voids; resource commitment; entry strategies; emerging economies; uncertainty